Sentiment Analysis on Islamic Capital Market during Covid-19 Pandemic - Siti Salmah; Siti Maysyaroh; Tri Nadia (Ekonomi Islam Indonesia, 2022)
This research was conducted to examine the Islamic capital market during the COVID-19 pandemic in Indonesia and in terms of scientific research in the journal published by Dimension. The method used is descriptive bibliometric statistical analysis and sentiment analysis from secondary data in the form of 203 papers published in the last 3 years, 2020 to 2022, then processed using VOSViewer, Microsoft Excel 2019 and SentiStrength. The results showed that bibliometric mapping was divided into 3 clusters; cluster 1 consists of 8 topics, cluster 2 consists of 11 topics and cluster 3 consists of 7 topics. Sentiment analysis from the literature shows good sentiment (positive) by 30%, bad sentiment (negative) by 21%, neutral sentiment by 48%, and the rest has a High Negative sentiment of 1%. This study found that during the pandemic the Islamic capital market trend fluctuated but still showed positive performance.